Can mandatory environmental information disclosure achieve a win-win for a firm's environmental and economic performance?. (20th March 2020) - Ren, Shenggang; Wei, Wenjuan; Sun, Helin; Xu, Qinyi; Hu, Yucai; Chen, Xiaohong
Abstract: Using the Guidelines of the Shanghai Stock Exchange on Environmental Information Disclosure for Listed Companies issued in 2008 as a quasi-natural experiment, we employ DID (difference in differences) model to identify the effects of China's mandatory environmental information disclosure (MEID) on a firm's environmental and economic performance. The results show that MEID has a positive impact on the firm's environmental performance, but has a negative impact on the firm's economic performance; MEID affects the firm's environmental and economic performance by increasing environmental management activities and costs; this policy has a more significant impact on the state-owned enterprises and small and medium enterprises than on non-state-owned enterprises and large enterprises. The results remain robust in a series of robustness tests. This study offers guidance for policymakers seeking to improve environmental information disclosure policies. Highlights: Explore the effects of MEID on the firm's environmental and economic performance. Employ DID model to identify the impact of the MEID on firm performance. MEID has a positive impact on environmental performance, but a negative impact on economic performance. MEID affects firm's environmental and economic performance by increasing environmental management costs.